2021
DOI: 10.3390/microorganisms9020317
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Viral Activity in the Surface Microlayer of the Arctic and Antarctic Oceans

Abstract: The ocean surface microlayer (SML), with physicochemical characteristics different from those of subsurface waters (SSW), results in dense and active viral and microbial communities that may favor virus–host interactions. Conversely, wind speed and/or UV radiation could adversely affect virus infection. Furthermore, in polar regions, organic and inorganic nutrient inputs from melting ice may increase microbial activity in the SML. Since the role of viruses in the microbial food web of the SML is poorly underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 72 publications
2
11
0
Order By: Relevance
“…The experiments in August showed the overall most clear effects of heterotrophic grazing in the two larger fractions, where the Synechococcus and bacterial abundances decreased markedly. Comparable reductions of the prokaryotic biomass in the <10-and the <90-µm fractions indicated that HNFs were the dominant bacterial grazers in August, in-line with previous studies identifying HNF (<5 µm) as the main top-down controller of bacterial abundance in the Arctic [57][58][59]. Furthermore, and similar to what Vaqué et al observed [60], we only found a correlation between the abundance of HNF and HNA bacteria (R 2 = 0.4580, p = 0.0453) and no significant correlation of HNF with the total bacteria abundance (Figure A5).…”
Section: Discussionsupporting
confidence: 90%
“…The experiments in August showed the overall most clear effects of heterotrophic grazing in the two larger fractions, where the Synechococcus and bacterial abundances decreased markedly. Comparable reductions of the prokaryotic biomass in the <10-and the <90-µm fractions indicated that HNFs were the dominant bacterial grazers in August, in-line with previous studies identifying HNF (<5 µm) as the main top-down controller of bacterial abundance in the Arctic [57][58][59]. Furthermore, and similar to what Vaqué et al observed [60], we only found a correlation between the abundance of HNF and HNA bacteria (R 2 = 0.4580, p = 0.0453) and no significant correlation of HNF with the total bacteria abundance (Figure A5).…”
Section: Discussionsupporting
confidence: 90%
“…Investigations on viruses in non-slick SML reported increased virus-mediated mortality, increased virus-like particle abundance, and higher virus-host ratios compared to underlying water [31,32]. Work on Lake Baikal described autochthonous bacteriophage communities establishing in the microlayer [33], but such studies are lacking for marine systems.…”
Section: Introductionmentioning
confidence: 99%
“…Overlaps between aerosols and rain samples must be treated with caution, because some rain could have reached the aerosol filter membrane during sampling and filter exchange (Table S5), although we tried to rule out the second possibility by subtracting reads from handling controls. Precipitation had the highest number of unique viruses (109), followed by foams (25), SSW (18), SML (7) and aerosols (6).…”
Section: Figure 3: Diversity and Enrichment Analysis Of Marine And Ai...mentioning
confidence: 99%
“…Like many micro- and macroorganisms 10,11 , viruses accumulate in the thin (<1 mm) uppermost layer of aquatic ecosystems, the surface microlayer (SML, reviewed by Cunliffe, et al 12 , Engel, et al 13 ), where they belong to a pool of organisms collectively referred to as neuston 14 . The enrichment of the virioneuston in the SML is mediated by bubble transport from the underlying water 15,16 and likely maintained by viral attachment to particles 17 and a dependency on abundant prokaryotic hosts 18 . In freshwater, bacteriophages residing in the SML can form autochthonous communities 19 but comparatively little viromics studies have been conducted for marine SML (reviewed by Rahlff 20 ).…”
mentioning
confidence: 99%